Structure of environmental data of experimental fields of embrapa/cpac using geographic information system - Sano, Edson Eyji; Assad, Eduardo Delgado; Moreira, Lucimar; Macedos, Jamil (Pesquisa Agropecuaria Brasileira, 1992)
This study aimed to arrange and quantify environmental data of eighteen experimental fields of EMBRAPA/CPAC, located in Planaltina (DF) using SGI/INPE (Geographic Information System developed by INPE). The data were arranged by digitalizing the following maps in scale of 1:40.000: Experimental field areas, Soils, Original Vegetation, Geomorphology and Slope. By overlaying the map of experimental field areas on the other maps, it was possibile to quantify the occupied areas into thematic classes for each experimental field. Some non-spatial, information such as crop types, soil amendments and preparation, seeding and harvest date, among others, were assembled using dBASE III PLUS data base. These informations can be easily accessed and processed with Geographic Information System, making them ready for association to the other codified data of a specific experimental field, hence the knowledge of land use history.